NCOG-37. NATURAL LANGUAGE ASSESSMENT CORRELATES WITH HEALTH-RELATED QUALITY OF LIFE IN ADULT GLIOMA PATIENTS. (9th November 2020) - Ammanuel, Simon; Almeida, Nyle; Kurteff, Garret; Kakaizada, Sofia; Molinaro, Annette; Berger, Mitchel; Chang, Edward; Hervey-Jumper, Shawn
Abstract: PURPOSE: Impairments of speech are common in glioma patients and negatively impact health-related quality of life. The benchmark for clinical assessments is task-based measures that miss essential components of quality of life status. In this study, we test the hypothesis that variations in natural language (NL) correlate with health-related quality of life status. MATERIALS AND METHODS: Natural language use was assessed using audio samples from 18 patients with newly diagnosed low- and high-grade gliomas collected unobtrusively. NL measures were correlated with the Quality of Life in Neurological Disorders (Neuro-QoL) outcomes at baseline. Spearman's rank-order correlation was used to determine relationships between Neuro-QoL scores and NL measures. RESULTS: Speech rate negatively correlated with functional domains of the Neuro-QoL (satisfaction with social roles: rho=-0.62, p=0.007; participate in social roles: rho=-0.74, p< 0.001;) while positively correlated with impairment domains(fatigue: rho=0.58, p=0.009). CONCLUSIONS: Assessments of baseline natural language may be a useful tool in the context of treatment planning and monitoring outcomes.